1995
DOI: 10.1002/path.1711770404
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up in early gastric cancer: Evaluation of prognostic factors

Abstract: Four hundred and fourteen cases of early gastric cancer (EGC), diagnosed between 1977 and 1993, were studied. The percentage of EGC increased from 1977 to 1984, but thereafter remained more or less stable, despite a continuous increase in the number of endoscopic examinations. Three hundred and ninety-six patients were followed up. Twenty-nine patients died from the tumour, giving a 5-year survival rate of 82.8 per cent. The 'large' size type of EGC, the presence of submucosal penetration, and lymph-node metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
3
27
1
1
Order By: Relevance
“…It is widely accepted that tumors with deep invasion or lymphatic invasion are more likely to involve lymph node metastasis [21][22][23]. We found that the incidence of lymph node metastasis detected by CK immunostaining was 19% in m-cancers but 35% in sm-cancers.…”
Section: Discussionmentioning
confidence: 67%
“…It is widely accepted that tumors with deep invasion or lymphatic invasion are more likely to involve lymph node metastasis [21][22][23]. We found that the incidence of lymph node metastasis detected by CK immunostaining was 19% in m-cancers but 35% in sm-cancers.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have reported that the 5-year and 10-year overall survival rates are 70.0-82.8% and 70.4-77.3%, respectively [2,6,8], and that 5-year and 10-year cancer-related survival rates are 91.7-98.3% and 87.8-95.2%, respectively [1,2,4,6,14,19]. The present results also showed excellent survival rates (5-year and 10-year [2] demonstrated that the overall survival rate of patients with EGC was equivalent to that of an age-matched and gender-matched control population.…”
Section: Discussionmentioning
confidence: 99%
“…Using univariate analysis, several authors have identified lymph node metastasis [1,4,6,7,8,14], macroscopic type [9], tumor size [6,7,9,14], depth of invasion [3,6,7,8,9], age [2,8,14], lymph node dissection [4], DNA ploidy status [2], Eastern Cooperative Oncology Group (ECOG) score [2] and histological type [14], as important prognostic factors in patients who undergo gastric resection for EGC. In the present study, significant differences in survival rate were found with respect to age, gender, tumor size, macroscopic type, histological grading, depth of invasion and lymph node metastasis, when analyzed using overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have demonstrated that early-stage gastric carcinomas with a high propensity for blood vessel invasion and lymph node metastasis show a worse prognosis because of early post-operative hepatic metastasis (Kodama et al, 1983;Orita et al, 1992). Recently, Ranaldi et al (1995) reported that in large early gastric cancers the presence of submucosal penetration and lymph node metastasis shows a highly significant association with a lower survival rate.…”
Section: Discussionmentioning
confidence: 99%